Heterogeneous Impacts of the Decentralization of Collective Bargaining - Antti Kauhanen; Terhi Maczulskij; Krista Riukula (The Research Institute of the Finnish Economy (ETLA), 2020)
This paper analyses the heterogeneous effects of the decentralization of collective bargaining on the incidence of wage increases and wage dispersion in Finland. We use linked employer-employee panel data for the 2005-2013 period, which includes major changes in bargain-ing systems and economic conditions. Our regression results from models with high-dimensional individual and firm fixed effects show that decentralized bargaining leads to very different outcomes for blue- and white-collar employees. Decentralized bargaining decreases wage dispersion among blue-collar employees and slightly increases it among white-collar employees. Decentralization also affects the incidence of wage in-creases differently for blue- and white-collar employees. We argue that these differences reflect the different preferences of the employee groups. We also show that the fallback option in local negotiations affects the decentralization outcomes.
Keywords: J31; J51; J52; 330; Decentralization; Collective agreements; Wage bargaining; Wage increase; Wage dispersion